Judicial and Legislative Interventions in the Prevention of Domestic Violence against Women: A Comparative Analysis of Title IV and V of the Violence Against Women Acts 1994 (USA) and the Protection of Women against Domestic Violence Act 2005 (India) - KN, Anitha (International Journal of Psychosocial Rehabilitation, 2025)
Domestic violence may be understood as the possible trace of the mainly patriarchal organization of societies, inducing hierarchical gender relations between men and women throughout the world.2 The societal dynamics enables the dominant sex to claim superiority in terms of hierarchical organisation between men and women that enables the establishment of patriarchies. Throughout the modern history, we see women being subjected to intense suppression by the society. The passive and active suppression dominates her life from cradle to the grave. These suppressions are supported by the family and society at all levels of her interactions. This Article contains compartitive study of Domestic Violence Act in India and Violence Against Women’s Act in USA.